2016
DOI: 10.3390/ijms17101770
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-1 Mediates Microglial Activation and Migration via the CK2 Pathway during Oxygen–Glucose Deprivation/Reperfusion

Abstract: Annexin-1 (ANXA1) has shown neuroprotective effects and microglia play significant roles during central nervous system injury, yet the underlying mechanisms remain unclear. This study sought to determine whether ANXA1 regulates microglial response to oxygen–glucose deprivation/reperfusion (OGD/R) treatment and to clarify the downstream molecular mechanism. In rat hippocampal slices, OGD/R treatment enhanced the ANXA1 expression in neuron, the formyl peptide receptor (FPRs) expression in microglia, and the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…The role of ANXA1 to inhibit and induce the secretion of pro-inflammatory and anti-inflammatory cytokines, respectively, has been fully described in different cells [46,47]. In fact, ANXA1 treatment reduced the elevated concentration of IL-6, TNFα and IL-4 in BV2 cells stimulated by synthetic amyloid peptide Aβ 1-42 [36], and the treatment of rat primary culture microglia with Ac2-26 reduced the LPS-induced secretion of IL1β and TNFα [48]. Here we confirm the anti-inflammatory profile elicited by exogenous ANXA1, since it elicited a reduction on LPS-induced TNFα and IL1β over secretion in BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ANXA1 to inhibit and induce the secretion of pro-inflammatory and anti-inflammatory cytokines, respectively, has been fully described in different cells [46,47]. In fact, ANXA1 treatment reduced the elevated concentration of IL-6, TNFα and IL-4 in BV2 cells stimulated by synthetic amyloid peptide Aβ 1-42 [36], and the treatment of rat primary culture microglia with Ac2-26 reduced the LPS-induced secretion of IL1β and TNFα [48]. Here we confirm the anti-inflammatory profile elicited by exogenous ANXA1, since it elicited a reduction on LPS-induced TNFα and IL1β over secretion in BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another study reported that during oxygen-glucose deprivation, ANXA1 promoted microglial activation and migration. 11 We therefore determined whether exogeneous ANXA1-induced SC cellular proliferation and migration, thus, leading to nerve regeneration.…”
mentioning
confidence: 99%
“…The neuroprotective effect of ANXA1 was explored and the findings indicate that ANXA1 promotes microglial activation and migration 38 .…”
Section: Discussionmentioning
confidence: 99%